Adequacy of dairy product intake among children in Kuwait using a short dietary assessment questionnaire. Issue 1 (16th October 2018) - Alkazemi, Dalal Usamah Zaid; Saleh, Asma
Abstract : Purpose: This paper aims to assess the consumption of dairy products in Kuwaiti children, and develop and validate a semi-quantitative food frequency questionnaire to measure dairy product consumption. Design/methodology/approach: This cross-sectional study was based on a sample of child–parent dyads ( n = 150). A dietary assessment questionnaire on local dairy products consumed by preschool and preadolescent children was developed. Serving and portion sizes were evaluated on the basis of the guidelines of the United States Department of Agriculture and the American Academy of Pediatrics to calculate median intake levels of three age groups (3-5, 6-8 and 9-11 years). Findings: All children met or exceeded the recommended daily servings of dairy products for their age and sex. Dairy product intake was often from processed dairy including milk-based desserts, flavored milk and cheese. Compared to boys, girls consumed more yogurt (15.5 per cent vs 14.2 per cent, p = 0.001) and milk-based desserts (15.5 vs 14.3, p = 0.001). In boys, flavored milk contributed more to the total dairy intake than in girls, especially in 6-8-year-olds (21.8 per cent vs 18.9 per cent, p = 0.021). Weight status was not associated with dairy product intake in either sex. Originality/value: This is the first study that quantifies dairy product consumption in Kuwaiti children and provides insight into sex-specific trends in dairy product selection. The findings of this study may help in investigating relationships between dairy product consumption in children and disease risk factors, and are important for the development of local dietary guidelines for children.